Enhancing the bio-epoxy composites with oil palm fibre as reinforcement: assessment of mechanical, physical and thermal properties - Senthilkumar, K.; Chandrasekar, M.; Jawaid, Mohammad; Fouad, Hassan; Abu-Jdayil, Basim (Springer, 2024)
In this work, short oil palm fibre-reinforced bio-epoxy matrix composites were fabricated using the hand-lay-up technique. The effects of oil palm fibre composites on mechanical, physical, and thermal behaviours were examined. This work aimed to identify the optimal fibre loading that enables the oil palm/bio-epoxy composite to have superior thermal and mechanical properties. Fibre loading varied from 30 to 60 wt%. A maximum Young’s modulus of 5.76 GPa was obtained at 60 wt% while a maximum flexural modulus of 5.2 GPa and impact strength of 5.55 kJ/m2 was obtained at 50 wt%. However, tensile and flexural strength were not much improved. Regarding the moisture absorption and thickness swelling, the composites followed a similar order: bio-epoxy matrix < 30 wt% < 40 wt% <50 wt% < 60 wt%. The fickian diffusion model was used to describe the thickness swelling behaviour. The major inference from the thermal characterization was that as the fibre loading was increased, there was a substantial improvement in thermal stability evident from the lower damping factor (0.21 at 60 wt.%), better dimensional stability and higher residue % (22.22% at 50 wt%) at elevated temperatures. Besides, scanning electron microscopy (SEM) was examined for tested samples to understand the fibre-to-matrix bonding phenomenon. Based on these results, the short oil palm fibre composites can be suggested for some potential applications such as automotive components (e.g., door trims, interior panels), aerospace (e.g., tray tables, overhead bins) and construction materials (e.g., cladding, roofing).